Understanding Accounting Students' Views on the Ethical Aspects of Creative Accounting - ANITA, Ni Kadek Nanda; SWASTI, Ni Komang Dinda; DEWI, Ni Putu Arinda Sukma; LESTARI, Ni Made Dian Dwi (Journal of Social Sciences and Cultural Study, 2025)
This study aims to understand accounting students' perspectives on ethical aspects of creative accounting practices through a literature review. The research method employs a descriptive qualitative approach with literature study from various scientific journals and academic publications. The research results reveal polarization of views among accounting students, where there are groups with negative perspectives who reject creative accounting practices and groups that are more tolerant towards such practices. This variation in perspectives is influenced by internal factors such as personal values, ethical understanding, and educational background, as well as external factors including social environment and industry pressure. Findings indicate that although students understand basic concepts of accounting ethics, their ability to identify ethical dilemmas in creative accounting practices remains limited. This ethics research emphasizes the urgency of strengthening education in accounting curricula to prepare future generations of accountants who can contribute positively to the credibility of the accounting profession.